Communication Pattern in Social Organization of Kampung Cempluk Tourism As the Realization of Campus Ring Village - Prasetyo, Redy Eko; Prasetyo, Bambang Dwi; Antoni, Antoni (Graduate School, Universitas Brawijaya, 2022)
The villagers are experiencing social problems such as shifting values, land transfer, complex regeneration of youth in agriculture, and land gentrification that make the community increasingly cornered. The firm conception of knowledge about the village plays a role in seeing the people as a lagging community. The presence of actors who parade the village community in Malang City brings a new concept, Kampung Cempluk tourism village, to support the community to move from the marginal condition. This study analyzes how communication patterns occur during the mobilization actors conduct social organizing when promoting the Kampung Cempluk tourism concept in Malang City. The method used is descriptive qualitative by applying interviews and technical data analysis to find in-depth findings. The research findings show that the communication process carried out by the mobilization actor can infiltrate the values of the social wisdom of the Cempluk community. This communication process occurs in various activities such as tahlilan (communal feast for event), prayer, or PKK (Family Welfare Program) meetings. Furthermore, this study shows that the process of transforming knowledge about Kampung Cempluk is directly conveyed through social routines. This social routine encourages the community to collectively agree on the Kampung Cempluk Festival (CVF), where social organizing is carried out in the movement process. The study results show that villagers who are known as disadvantaged groups can pattern complementary communication into symmetrical communication. Submission of concepts by village movers triggers a collective spirit among them and direct action in maximizing the implementation of CVF, and then increases social relations with other stakeholders such as university students, lecturers, and sponsorship. Keywords: communication patterns, kampung cempluk festival, social organizing, tourism.